(untitled) (Biological Sciences - PJSIR, 2009)
Pakistan is situated between latitude 240 and 370 North and longitude 620 and 750 East, on the eastern part of the Arabian Sea with a coastline of about 900 km. Lobsters are found both on its northwest (Balochistan) and southeast coasts (Sindh). Important fishing grounds of lobsters are located along Ormara, Pasni Gwader and Jiwani besides Karachi coast. Todate, 16 species of lobsters have been recorded from Pakistan. The only predominant commercial species is Panulirus polyphagus, which constitutes 83% of the catch. The paper provides an identification key for northern Arabian Sea lobsters and outlines the available information on the biology, fisheries and management of the lobster species from Pakistan. Most of the studies have been focused on P. polyphagus.